Perceptions of Clinical Education Preparedness at a Large Urban US University: Is There a Difference Between US-Born and Non-US Born Students? - Cohen, Timmerie; Justice, M. Ferell; Dempsey, Melanie C. (Journal of International Students, 2014)
This research compared three clinical preparedness domains, communication ability, social comfort, and clinical confidence, between US-born and non-US born radiation sciences students. The aim of the study was to determine if there were perceived differences in clinical preparedness between them. Student’s place of birth was found to be an influencing factor in each of the clinical preparedness domains. Informing faculty, clinical instructors, and hospital staff of the perceived differences in clinical education preparedness among non-US born students may serve as a catalyst for instructional change. Educators can then formulate instructional strategies to better prepared non-US born students.